Isolation and purification of STEAP1 protein fragment in Escherichia coli cells: a potential target for prostate cancer - Ferreira, Jorge Daniel Barroca (2016)
Prostate cancer is the second most prevalent type of cancer worldwide and the sixth cancer-related death. The current applied therapies in advanced cancer stages are limited and not completely efficient. Thus, it is necessary to develop alternatives using, for example, molecular biology vanguard technologies that allow to identify genes that encode transmembrane proteins, abundantly expressed in cancer tissues. The six-transmembrane epithelial antigen of the prostate (STEAP1) was recognized as a protein presenting a structure with six transmembrane domains connected by extracellular loops. It is commonly located in plasma membrane, for example in communication junctions or even in endosomal membranes, suggesting a role as ion channel or transporter protein in intracellular communication between tumor cells. In association with its high specificity and significant expression levels in prostatic cancer tissues, STEAP1 is a promising candidate to be imposed as a therapeutic target, especially for immunotherapy. However, the impossibility of large-scale production hinders the development of structural and biointeraction studies, not only to establish the tridimensional structure of STEAP1 but also to understand its vivo behavior. Therefore, the main objectives consisted in establish the culture medium formulation and optimal fermentation conditions in order to achieve a maximum yield for the STEAP1 first loop (STEAP11-142) biosynthesis, besides access several conditions inherent to immobilized metal affinity chromatography (IMAC) to obtain considerable levels of purified peptide. The main results showed that TB medium fermentation at 37 ºC, 250 rpm and pH 7.2 over 8 hours increased the STEAP11-142 biosynthesis levels. Moreover, Triton X-100 at 1 % (v/v) demonstrated to be the most effective detergent for protein recovery. This result was validated by Western-blotting analysis which revealed a single immunoreactive band with the expected molecular weight (17-25 kDa). Concerning the purification step by IMAC, we tested two resins charged with nickel and cobalt. The results lead to a typical chromatographic profile where the target fragment was completed retained. Nevertheless, a considerable amount of heterologous proteins from Escherichia coli (E. coli) host co-eluted with the STEAP11-142 fragment, being necessary to develop an alternative elution strategy and optimize the purity of the target fractions.